PREPARING YOUR STUDENTS FOR MAIN ACTIVITY - Mohammad Fernanda Levigta (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
Teaching students are known to be challenging. Among the challenges are that students have short attention span, love to spend most of their time playing, and often talk with their peers. Furthermore, in the context of learning English as a second language, simple distraction can be a good escape for them from studying. This will result in problems for the teacher. Therefore, teaching time should be meaningful for the students to be able to learn. In creating meaningful learning experience, teacher prepares the students to be ready for the lesson, makes students understand what and why they are learning it, and how they are going to learn it. It is the task of the teacher to ensure such process to happen. The presentation will describe my experience about how I ensure the above process to take place. Learning my lesson that my students were detached from the lesson I was giving, I changed the way I start the lesson in my class at a pre-school in Jakarta. I used some techniques to manage the class, namely “Presentation, Practice, and Production (PPP), and also used “Audio-Lingualism” method. These are considered to be the solution for me in grabbing their attention, in order to make them fully understand the lesson. The presentation is expected to be attended by English teachers, teacher trainers, and those who are interested in the area of teaching English to young learners.